Microwave properties and absorption characteristics of yig – tpnr composites / M. Abdul Aziz … [et al.] - Abdul Aziz, M.; Mustaffa, H. A.; Sahrim, H. A.; A.H., Siti Atkah (2002)
Yttrium iron garnet (YIG) - thermoplastic natural rubber (TPNR) magnetic composites with 10 - 30 weight percent of YIG filler were prepared via a Brabender plasticorder internal mixer. Their microwave electromagnetic properties and absorption characteristics at room temperature (299 K) were studied in the range of 0.3 to 13.5 GHz using a microwave vector network analyzer (MVNA) . The real and imaginary components of the relative complex dielectric permittivity ( ɛ:r*= ɛr1 – jɛr” ) and magnetic permeability (µr* = µr' - jµr" ) were computed from the reflection and transmission complex scattering parameters (S11* and S21*) using the Nicolson-Ross and Precision models. The result shows that the reflection coefficient (I) strongly depends on the thickness and the electromagnetic properties of the samples.